Language Choice Form of Multi Ethnic Community in Family Area at Permai ATM Housing - Rahmasari, Dian; Zulaeha, Ida (Pascasarjana Universitas Negeri Semarang, 2018)
The purpose of this study is to identify and analyze the language choice of multi-ethnic community in family area at Permai ATM Housing. The data collected through the refer method consists of basic and advanced technique,                                   the basic technique was tapping technique, and advanced techniques, namely I: a technique of speech live free refer (SBLC), technique II: recording technique, technique III: record technique. The determinant unsure technique (PUP) and the differential distinguishing technique (HBB) were used to analyze the data. The language choice of multi-ethnic community in the family area at Permai ATM Housing included single variations of languages covered Malay-Banggai, Banggai, Saluan, Balantak, Banjar, and Bugis; codes switch included Saluan to Bahasa Indonesia, Banjar to Malay-Banggai; and code mixes included word insertion of Malay-Banggai, into Bahasa Indonesia and Banggai to Malay-Banggai, phrase insertion included Saluan to Bahasa Indonesia and Malay-Banggai to Bahasa Indonesia, and baster insertion included Banggai into Bahasa Indonesia.